Management of the program brand in front of the corporate brand in social media. Case: Money Heist - Pereira-Villazón, Tatiana; Portilla, Idoia (Estudios sobre el Mensaje Periodístico, 2020)
ue to the development of digital television and the arrival of new platforms, the institutions of the Spanish audio-visual sector had to develop new communication strategies for their brands. Among the communication channels they can use, social networks occupy a prominent place.This paper examines the case of La casa de papel. It analyses the communication of Atresmedia, Netflix España and Vancouver Media in their corporate and the program accounts on Twitter, Facebook and Instagram. The study period includes two weeks before and after the launch of the third season of this series on July 19, 2019.With a total of 748 tweets, we show that the communication of the brand La casa de papel in social networks made by Atresmedia, Netflix Spain and Vancouver Media is different in the number of publications, use of resources and the role of the corporate brand.